Follicular Thyroid Adenoma with Papillary Architecture - Jose Carnate (Philippine Journal of Otolaryngology Head and Neck Surgery, 2023)
A 23-year-old woman underwent left thyroid lobectomy and isthmusectomy for a 2 cm diameter firm mass on the left side of the neck that was also visualized on ultrasonography. The specimen consisted of a 22-gram thyroid gland composed of the left lobe, isthmus and a pyramidal lobe. Cut section of the left lobe showed a 3.5 cm diameter solitary, discrete and encapsulated mass with a tan lobulated and solid cut surface. The rest of the thyroid tissues had red-brown meaty cut surfaces.